1974
DOI: 10.1029/jc079i036p05633
|View full text |Cite
|
Sign up to set email alerts
|

Sofar channel axial sound speed and depth in the Atlantic Ocean

Abstract: Axial sound speed and depth of the Sofar channel in the north and south Atlantic have been estimated and the seasonal variations that affect Sofar propagation examined. The estimates are derived from applying averaging techniques to archived oceanographic data. The computed values appear to agree within one part per thousand with the measured data from long‐range propagation experiments. A more accurate sound speed mapping method is recommended, as is the incorporation of measured values of speed and depth in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 20 publications
3
9
0
Order By: Relevance
“…Therefore the temperature inversion occurred in shallow water is shown that in the sound source is located nearby the temperature inversion layer depth the sound is well propagated far. This result was similar to the structure of sound wave poroagation characteristic shown as SOFAR channel in the deep sea [4].…”
Section: Acoustic Propagation Model Resultssupporting
confidence: 87%
“…Therefore the temperature inversion occurred in shallow water is shown that in the sound source is located nearby the temperature inversion layer depth the sound is well propagated far. This result was similar to the structure of sound wave poroagation characteristic shown as SOFAR channel in the deep sea [4].…”
Section: Acoustic Propagation Model Resultssupporting
confidence: 87%
“…Indeed, icegenerated ambient noise near the ocean surface in the Polar regions (e.g., due to loud iceberg cracking events, with levels up to 245 dB re 1 μPa at 1 m) can efficiently couple directly to the SOFAR channel. This coupling is due to the natural descent of the SOFAR channel axis from the sea surface in the Polar regions toward greater depths at the lower latitudes where the Ascension and Wake Island sites are located [Chapp et al, 2005;Matsumoto et al, 2014;Northrop and Colborn, 1974]. When using averaging durations shorter than 1 year, the observed seasonal variability of the amplitude of the coherent SOFAR arrivals confirms the Polar origin of the dominant component of the ambient noise generating these arrivals (see supporting information Figure S6).…”
Section: Passive Acoustic Thermometry Of the Deep Oceanssupporting
confidence: 55%
“…However, the RAM model predicts that acoustic phases partially propagate as surface reflected waves south of the 60°S parallel, thereby evading bathymetric obstruction and reducing the average effect of acoustic blockage to ~10 dB re 1 μPa. This upward shift of the axis of the SOFAR channel is facilitated by the temperature anomaly of the ACC, which dilutes vertical sound speed gradients in the upper layers and subsequently raises the minimum velocity zone to shallower depths of up to 300 m and less (e.g., Northrop and Colborn [] and de Groot‐Hedlin et al []; see also Figure S3). Similar effects of range‐dependent temperature variations on high‐latitude acoustic propagation have been previously observed by Chapp et al [], enabling long‐distance detection of iceberg‐generated tremor in the southern Indian Ocean.…”
Section: Investigation Of Potential Bathymetric Blockage and Transmismentioning
confidence: 99%